The impact of water pollution on environmental health in the context of household waste - Lutpi, Nabilah Aminah; Nabil, Ahmad Jazuly (Environmental and Toxicology Management, 2024)
Water pollution is one of the environmental problems that is increasingly urgent to be addressed, especially those caused by household waste. This waste, if not managed properly, can contain various hazardous chemicals and microorganisms that contaminate water sources. Descriptive analysis to describe the pollution phenomenon in depth through narrative analysis of community experiences and the socio-economic impacts of pollution. Results: Water pollution caused by household waste is a serious problem that affects environmental and human health. Polluted water can contain bacteria and parasites that cause diarrhea, dehydration, and malnutrition. Household waste can cause ecosystem damage, the life of aquatic biota is disrupted due to decreased water quality. Water pollution due to household waste has a broad impact on human health and the environment. Good waste management efforts are essential to prevent further pollution and protect public health and ecosystems.